NEW MEASURES OF THE COSTS OF UNEMPLOYMENT: EVIDENCE FROM THE SUBJECTIVE WELL-BEING OF 3.3 MILLION AMERICANS. - HELLIWELL, JOHN F.; HUANG, HAIFANG (Economic Inquiry, 2014)
Using two large U.S. surveys, we estimate the effects of unemployment on the subjective well-being (SWB) of the unemployed and the rest of the population. For the unemployed, the nonpecuniary costs of unemployment are several times as large as those resulting from lower incomes, while the indirect effect at the population level is 15 times as large. For those who are still employed, a one percentage point increase in local unemployment has an impact on well-being roughly equivalent to a 4% decline in household income. We also find evidence indicating that job security is an important channel for the indirect effects of unemployment. ( JEL E24, H23, J64, J68)